Blocking IL-19 Signaling Ameliorates Allergen-Induced Airway Inflammation - Weng, Yun-Han; Chen, Wei-Yu; Lin, Yen-Lin; Wang, Jiu-Yao; Chang, Ming-Shi (Frontiers in Immunology, 2019)
Asthma is a chronic inflammatory disease of the airway. Its major symptoms are reversible breathing problems causing airway narrowing and obstruction. IL-19 is a member of the IL-10 family cytokines. We previously showed that IL-19 induces T-helper 2 (Th2) cytokines and that asthma patients had higher serum IL-19 levels. To further examine whether inhibiting IL-19 and its receptor (IL-20R1) protected rodents against asthma, we used Dermatophagoides pteronyssinus (Der p; house dust mites) to induce chronic airway inflammation in wild-type C57BL/6 and IL-20R1-deficient mice and then analyzed the effect of the IL-20R1 deficiency on the pathogenesis of asthma. We also examined whether inhibiting IL-19 and IL-20R1 ameliorated Der p-induced chronic asthma. Der p induced IL-19 in lung airway epithelial cells, type 2 alveolar cells, and alveolar macrophages. An IL-20R1 deficiency abolished IL-19-induced Th2 cell differentiation in vitro. Th2 cytokine expression, immune cell infiltration in the bronchoalveolar lavage, airway hyperresponsiveness (AHR), and bronchial wall thickening were lower in Der p-challenged IL-20R1-deficient mice. Anti-IL-20R1 monoclonal antibody (mAb) 51D and IL-19 polyclonal antibody (pAb) both ameliorated Der p-induced airway hyperresponsiveness, lung immune cell infiltration, bronchial wall thickening, and Th2 cytokine expression. Moreover, we confirmed that anti-IL-19 mAb (1BB1) attenuated lung inflammation in a rat ovalbumin-induced asthma model. This is the first report to show that inhibition of IL-19 by targeting IL-19 or IL-20R1 protected rodents from allergic lung inflammation. Our study suggests that targeting IL-19 signaling might be a novel therapeutic strategy for treating allergic asthma.